Co-firing of biomass in coal fired boilers – status and lab scale studies - Vuthaluru, Hari; Shah, K. (ICHT, 2013)
One of the most attractive and easily utilizable renewable energy sources for co-firing technologies is biomass which can be fired up to 20% with coal in existing pulverized coal (pc) fired boilers. When biomass is used as a supplemental fuel in an existing coal boiler, this renewable energy source can provide several benefits including reduced gaseous emissions. However, there are several operational bottlenecks in 1terms of ash related issues. Our studies with European collaborator for nearly decade dealt with ash related issues covering ash transformation mechanisms for both pc-fired boiler environments with the objective of developing a Co-firing Advisory Tool (CAT). Some of the research outcomes to date along with status on co-firing activities are addressed in this paper. The studies towards the development of CAT addressed in this collaborative venture are expected to benefit power utilities in making informed decisions while selecting the renewable energy resources for power generation.